Metformin as a disease-modifying therapy in osteoarthritis: bridging metabolism and joint health - Halabitska, Iryna; Petakh, Pavlo; Kamyshnyi, Oleksandr (Frontiers in Pharmacology, 2025)
BackgroundOsteoarthritis (OA) and impaired glucose tolerance (IGT) frequently coexist, leading to compounded clinical and metabolic challenges. This study investigates the effects of metformin in improving both clinical outcomes (pain, stiffness, physical function) and metabolic parameters (inflammatory markers, lipid profile, BMI) in patients with knee OA and IGT.MethodsThe study included 60 patients diagnosed with knee OA and IGT. Participants were divided into two groups: 26 patients received standard OA treatment without metformin (Without Metf), while 34 received metformin (500 mg twice daily) for 3 months, in addition to standard treatment (With Metf). Clinical assessments (WOMAC, Lequesne Algofunctional Index, KOOS, VAS) and metabolic markers (CRP, NLR, SOD, lipid profile, BMI) were measured before treatment, after 1 month, and after 3 months.ResultsThe With Metf group showed significantly greater improvements in pain, stiffness, physical function, and quality of life compared to the Without Metf group. Metformin also led to significant reductions in inflammatory markers and improvements in lipid profiles and metabolic health indicators. The With Metf group demonstrated enhanced BMI, waist-to-hip ratio, and waist-to-height ratio. Furthermore, the need for increased NSAID doses was predicted by factors such as pain severity and inflammatory markers.ConclusionMetformin effectively alleviates osteoarthritis symptoms and improves metabolic health in patients with both OA and IGT. Further research is needed to explore its long-term effects on joint health, inflammatory markers, and its potential role in OA management in patients without IGT.